2007
DOI: 10.1002/humu.20431
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, parental germline origin, and phenotypic spectrum of de novoHRASmissense changes in Costello syndrome

Abstract: Activating mutations in v-Ha-ras Harvey rat sarcoma viral oncogene homolog (HRAS) have recently been identified as the molecular cause underlying Costello syndrome (CS). To further investigate the phenotypic spectrum associated with germline HRAS mutations and characterize their molecular diversity, subjects with a diagnosis of CS (N = 9), Noonan syndrome (NS; N = 36), cardiofaciocutaneous syndrome (CFCS; N = 4), or with a phenotype suggestive of these conditions but without a definitive diagnosis (N = 12) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
129
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(142 citation statements)
references
References 52 publications
13
129
0
Order By: Relevance
“…His parents declined autopsy examination. [Aoki et al, 2005;Estep et al, 2006;Kerr et al, 2006], three with neuroblastoma [Aoki et al, 2005;Zampino et al, 2007;van der Burgt et al, 2007], one with transitional cell carcinoma , and two unspecified tumors [Zampino et al, 2006]. Congenital heart defects.…”
Section: Deathsmentioning
confidence: 99%
See 1 more Smart Citation
“…His parents declined autopsy examination. [Aoki et al, 2005;Estep et al, 2006;Kerr et al, 2006], three with neuroblastoma [Aoki et al, 2005;Zampino et al, 2007;van der Burgt et al, 2007], one with transitional cell carcinoma , and two unspecified tumors [Zampino et al, 2006]. Congenital heart defects.…”
Section: Deathsmentioning
confidence: 99%
“…Phenotypic features of Costello syndrome include polyhydramnios, increased birth weight, feeding problems, failure to thrive, short stature, developmental delay, pleasant personality, characteristic facial appearance, soft skin, papillomata, spatulate fingerpads, deep palmar creases, joint and skin laxity, kyphoscoliosis, pectus, and splayed fingers with ulnar deviation. Since the discovery that HRAS gene mutations cause Costello syndrome [Aoki et al, 2005], at least 150 genotyped patients have been studied [reviews by Estep et al, 2006;Gripp et al, 2006;Kerr et al, 2006;Zampino et al, 2007]. Consensus expert opinion recommends that Costello syndrome be defined solely by HRAS mutations , which differs from the molecular heterogeneity of CFC syndrome and Noonan syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…The number of fatal cases was 5/138 patients with p.G12S, 4/6 with p.G12C, 3/17 with p.G12A, 3/4 with p.G12D, 2/2 with p.G12V, 1/1 with p.G12E and 1/1 with p.E63K. 3,[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] The mortality of patients with p.G12C or p.G12D was significantly higher than that of the patients with the more common p.G12S (P¼0.026 by Fisher's exact test). Previous studies have shown that the p.G12V substitution has the highest transformative potential (p.G12V4p.G12A, p.G12S, p.G12C, p.G12D4p.G13D) and is the most frequently found mutation in human tumors.…”
Section: Discussionmentioning
confidence: 99%
“…3 It has been suggested that the CS diagnosis should be applied only to patients with a mutation in HRAS because of the high risk of malignancies associated with HRAS mutations and the relative homogeneity of the CS phenotype. 4 A total of 14 HRAS missense mutations and one duplication mutation have been reported in 185 patients with CS 3,[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] or congenital myopathy with excess of muscle spindles. 24 Most of these mutations have previously been reported as somatic and oncogenic mutations in various tumors.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Recently, Costello syndrome has been identified as the first example of a disorder associated with activating germ-line mutations in the HRAS proto-oncogene. [10][11][12][13][14][15][16][17] In addition to Costello syndrome, a group of multiple congenital anomaly syndromes collectively named RASopathies have been shown to be associated with germline mutations in various genes of the RAS/MAPK pathway. 8,18,19 Indeed, inhibitors of a number of components of the RAS/MAPK pathway are currently being evaluated as pharmacological interventions in RASopathies.…”
Section: Introductionmentioning
confidence: 99%